MuSK-Associated Myasthenia Gravis: Clinical Features and Management - Rodolico, Carmelo; Bonanno, Carmen; Toscano, Antonio; Vita, Giuseppe (Frontiers in Neurology, 2020)
Muscle specific tyrosine kinase Myasthenia Gravis (MuSK-MG) is a rare, frequently more severe, subtype of MG with different pathogenesis and peculiar clinical features. The prevalence varies among countries and ethnic groups affecting 5-8 % of all MG patients. MuSK-MG usually has an acute onset affecting mainly facial-bulbar muscles. Symptoms usually progress rapidly, within a few weeks. Early respiratory crises are frequent. The disease may lead to generalized muscle weakness up to muscle atrophy. The main bulbar involvement, the absence of significant thymus alterations, and the association with HLA class II DR14, DR16, DQ5 alleles have been confirmed. Atypical onset, such as ocular involvement, lack of symptoms fluctuations, acetylcholinesterase inhibitors failure, and negative results of electrophysiologic testing, if not specifically performed in the mainly involved muscles groups, make MuSK-MG diagnosis challenging. In most cases steroids are effective. Conventional immunosuppressants are not commonly able to replace steroids in maintaining a satisfactory long-term control of symptoms. However, the majority of MuSK-MG patients are refractory to treatment. In these cases, the use of rituximab showed promising results, resulting in sustained symptom control.